"Hogg, Richard (General Ed.) (1992): The Cambridge History of the English Language. Volume I: The Beginnings to 1066, Edited by Richard M. HogG. Cambridge: Cambridge University Press." - Guzmán, Trinidad (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen